Instructors’ Perceptions of Using Videos in Flipped Learning: A Reflective Study on Online Discussion Classes - Chien, Posheng Vincent; Dzabelova, Inna; Gupta, Charu; Wee, Zi Ning (International Journal on Open and Distance e-Learning, 2021)
Since most of the university courses in Tokyo shifted to online mode, instructors were forced to adapt to different teaching approaches and maintain quality education. This reflective paper investigates perceptions of instructors in using videos in flipped learning in online discussion classes. To maximize student speaking time and practice opportunities, they decided to implement flipped learning by creating videos explaining the target discussion skills for each lesson and posting them in an online learning management system (LMS). The students were required to complete their pre-learning in preparation for classroom activities with their instructors or their peers. Pre-learning involved having the students watch the video at any time in the week before the lesson and completing a connected task. When the students come to class, they could start to apply, analyze, evaluate, and produce meaningful, interactive, and rich discussions. After implementing flipped learning and pre-lesson tasks for one semester, the instructors reflect on and discuss their experiences and observations. This study analyzed and discussed the advantages and disadvantages of flipped learning. On one hand, it helped save time spent on online instruction, offered learners a chance to control their learnings, and helped students at different levels. On the other hand, learners and instructors also faced some challenges, such as time consumption and low motivation. The paper concluded with the study limitations and suggestions for future implementation in online, face-to-face, and hybrid settings.